A scenario‐drafting study to explore potential future implementation pathways of circulating tumor DNA testing in oncology - Astrid Kramer; Carmen Rubio‐Alarcón; Daan van denBroek; Daan C. L. Vessies; Iris van't Erve; Gerrit A. Meijer; Geraldine R. Vink; Ed Schuuring; Remond J. A. Fijneman; Veerle M. H. Coupé; Valesca P. Retèl (Molecular Oncology, 2024)
Circulating tumor DNA (ctDNA) detection has multiple promising applications in oncology, but the road toward implementation in clinical practice is unclear. We aimed to support the implementation process by exploring potential future pathways of ctDNA testing. To do so, we studied four ctDNA‐testing applications in two cancer types and elicited opinions from 30 ctDNA experts in the Netherlands. Our results showed that the current available evidence differed per application and cancer type. Tumor profiling and monitoring treatment response were found most likely to be implemented in non‐small cell lung cancer (NSCLC) within 5 years. For colorectal cancer, applications of ctDNA testing were found to be at an early stage in the implementation process. Demonstrating clinical utility was found a key aspect for successful implementation, but there was no consensus regarding the evidence requirements. The next step toward implementation is to define how clinical utility of biomarkers should be evaluated. Finally, these data indicate that specific challenges for each clinical application and tumor type should be appropriately addressed in a deliberative process involving all stakeholders to ensure implementation of ctDNA testing and timely access for patients.